Phytosterols in rice bran and their health benefits - Liu, Zhaoguo; Liu, Xiaoxiao; Ma, Zheng; Guan, Tianzhu (Frontiers in Nutrition, 2023)
With the continuous technological innovation in the high-value utilization of rice bran byproducts, rice bran oil retains a higher concentration of beneficial components such as a well-balanced composition of fatty acids and abundant phytosterols. This makes it a highly nutritious and healthy vegetable oil. This review provides an overview of the advancements made in separating, purifying, and processing phytosterols in rice bran oil. The review also introduces techniques for assessing the stability of rice bran oil.Moreover, the review emphasizes the nutritional value of phytosterols found in rice bran oil, highlighting their various health benefits, including their anticancer, antiinflammatory, anti-allergic, antibacterial, cholesterol-lowering, skin-protective, antiobesity, anti-diabetic, neuroprotective, gastroprotective, and immune-enhancing effects.Attaining a comprehensive understanding of the research progress made in phytosterols derived from rice bran oil can offer valuable guidance for the efficient utilization of rice bran.